El presente en función del futuro en polaco y en español - Perlin, Jacek (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
In both Polish and Spanish languages a possibility exists to use the present tense to express a future action of state. In this paper some remarks about the differences in reference to this phenomenon between the mentioned tongues have been presented. Polish language when compared to Spanish reveals more restrictions, it means there are fewer possibilities of using present tense. In Spanish when the context permits to determine the future moment the present tense can always be used.
The present tense in function of future in Polish and Spanish